Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007877.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Haemostatic drugs for traumatic brain injury

Abstract: Background Traumatic brain injury (TBI) is a leading cause of death and disability. Intracranial bleeding is a common complication of TBI, and intracranial bleeding can develop or worsen after hospital admission. Haemostatic drugs may reduce the occurrence or size of intracranial bleeds and consequently lower the morbidity and mortality associated with TBI. Objectives To assess the effects of haemostatic drugs on mortality, disability and thrombotic complications in patients with traumatic brain injury. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Tranexamic acid was evaluated in a subset of patients in the CRASH-2 trial and showed a trend but no significant difference toward reduced mortality and intracranial hemorrhage growth at 24 to 48 hours . The results from the CRASH-2 trial have been consistent with a subsequent randomized controlled trial evaluating tranexamic acid (Yutthakasemsunt et al, 2013) and an earlier systematic review on the use of hemostatic agents following TBI (Perel et al, 2010). Clinical evaluation of tranexamic acid remains ongoing in the CRASH-3 trial (NCT01402882) which is an international randomized controlled trial (Dewan et al, 2012).…”
Section: Mechanisms Of Injurysupporting
confidence: 53%
“…Tranexamic acid was evaluated in a subset of patients in the CRASH-2 trial and showed a trend but no significant difference toward reduced mortality and intracranial hemorrhage growth at 24 to 48 hours . The results from the CRASH-2 trial have been consistent with a subsequent randomized controlled trial evaluating tranexamic acid (Yutthakasemsunt et al, 2013) and an earlier systematic review on the use of hemostatic agents following TBI (Perel et al, 2010). Clinical evaluation of tranexamic acid remains ongoing in the CRASH-3 trial (NCT01402882) which is an international randomized controlled trial (Dewan et al, 2012).…”
Section: Mechanisms Of Injurysupporting
confidence: 53%
“…No reliable evidence from RCTs exists to support the effectiveness of haemostatic drugs in reducing mortality or disability in patients with TBI [513]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, novel diagnostic tools may enhance our insight into the contribution of fibrinogen and platelets to clot formation and fibrinolysis, thereby enhancing our knowledge about the pathophysiological mechanisms underlying the development of coagulopathy in isolated TBI. Moreover, the insufficient evidence for the effectiveness of administration of coagulation factors like heparin, antifibrinolytics, or recombinant factor VII, as treatment for TBI-associated coagulopathy, prohibits the design of an effective therapeutic regimen in these patients (Pahatouridis et al, 2010;Perel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%